Accounting Information System using Midtrans Payment Gateway for Sport Equipment Business - Marcella Vania Kurniawan; Agnes Advensia Chrismastuti; Andre Kurniawan Pamudji (Soegijapranata Catholic University, 2026)
This study aims to implement an integrated Accounting Information System (AIS) with Midtrans payment gateway at Toko Sahabat, a sports equipment store in Semarang, Indonesia. Through primary and secondary data collection, including interviews, direct observation, and documentation analysis, this study aims to analyze the accounting challenges faced by Toko Sahabat and design solutions accordingly. The results show that AIS implementation brings significant benefits in inventory management, transaction recording, and financial statement preparation, giving stores a competitive advantage in an increasingly competitive business environment.